Mobile and more productive? Firm-level evidence on the productivity effects of mobile internet use at the early stage of diffusion - Irene Bertschek; Thomas Niebel (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2013)
Mobile internet access allows for flexibility with respect to working time and working place. We analyse whether employees' use of mobile internet access improves firms' labour productivity. Our data set comprises 2460 German firms and refers to the year 2010, when mobile internet started its diffusion process to firms on a large scale. The econometric analysis shows that firms' labour productivity significantly increases with the share of employees with mobile internet access. However, an instrumental variable approach reveals that mobile internet use does not cause higher labour productivity.
urn:nbn:de:bsz:180-madoc-353952
Keywords: D22; L20; O33; 330; Mobile Internet; Labour Productivity; Firm-Level Data